The impact of stock liquidity on trade credit: empirical evidence from Vietnam - Nguyen Van, Ha (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study analyzes the influence of stock liquidity on firms’ provision of trade credit, using a sample of 3,218 observations of firms listed on the Ho Chi Minh City Stock Exchange (HOSE) during the period 2006–2024. The empirical results show that the relationship between stock liquidity and trade credit is positive and statistically and economically significant, indicating that firms with highly liquid stocks tend to provide more trade credit. These results remain robust across different measures of variables, alternative model specifications, and controlling for endogeneity. From a policy perspective, the study emphasizes the importance of improving stock market liquidity as a channel to support trade credit provision, thereby contributing to supply chain development and economic growth.